2015
DOI: 10.1097/mpg.0000000000000695
|View full text |Cite
|
Sign up to set email alerts
|

Early Introduction of Complementary Foods in Preterm Infants

Abstract: Preterm infants are significantly more likely to be introduced to complementary foods early compared with term infants. The predictors of early solid feeding differ for preterm infants. Given the health implications, specific guidelines for preterm infants should be developed and future research should examine predictors of early introduction in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 36 publications
7
42
1
1
Order By: Relevance
“…Research has pointed out that preterm infants are significantly more likely to be introduced to solid foods earlier compared with term infants. Observational studies have pointed out that preterm infants start complementary feeding between 11.5 and 15.1 weeks corrected age [33-36]. Even though a large amount of children are born premature every year, this systematic review shows that well-designed studies on which guidelines about the timing of initiating complementary feeding in preterm infants and the effect on overweight can be based are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Research has pointed out that preterm infants are significantly more likely to be introduced to solid foods earlier compared with term infants. Observational studies have pointed out that preterm infants start complementary feeding between 11.5 and 15.1 weeks corrected age [33-36]. Even though a large amount of children are born premature every year, this systematic review shows that well-designed studies on which guidelines about the timing of initiating complementary feeding in preterm infants and the effect on overweight can be based are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The time of introducing solids was measured in weeks rather than months which allows for precise measurement of the time of event (i.e., the age of introducing solids) and clearly described early introduction of solids as "before 17 weeks". Many studies [34,46] report infant feeding patterns in months and define early introduction of solids as "before 4 months" and it therefore remains unclear if this refers to completed months of age. Researchers also do not provide a standardised criterion for converting months to weeks or vice versa and these conversions are often inconsistently determined and reported.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Braid et al 7 , Jonsson et al 9 and Rodrigues and Delgado 8 report that the incorporation of supplementary feeding started earlier in preterm infants than in full-term infants (3.25 months of corrected age in preterm infants versus 4.25 to 4.5 months in full-term infants).…”
Section: Age Of Incorporation Of Supplementary Foodsmentioning
confidence: 99%
“…In spite of the above, a significant number of studies were found in literature suggesting, that in preterm infants, solid foods are introduced even before 4 months, as mentioned in Braid et al 7 , Rodrigues and Delgado 8 , Jonsson et al 9 and Chung et al 10 .…”
mentioning
confidence: 97%
See 1 more Smart Citation